Dibenzylammonium hydrogen maleate and a redetermination at 120 K of bis(dibenzylamino)methane. (24th June 2013) - Castillo, Juan C.; Abonía, Rodrigo; Cobo, Justo; Glidewell, Christopher
<x xml:space="preserve">Abstract</x> In dibenzylammonium hydrogen maleate [or dibenzylammonium (2Z)‐3‐carboxyprop‐2‐enoate], C14H16N+·C4H3O4−, (I), the anion contains a fairly short and nearly linear O—H...O hydrogen bond, with an O...·O distance of 2.4603 (16) Å, but with the H atom clearly offset from the mid‐point of the O...O vector. The counter‐ions in (I) are linked by two N—H...O hydrogen bonds to form C22(6) chains and these chains are weakly linked into sheets by a C—H...O hydrogen bond. Bis(dibenzylamino)methane, C29H30N2, (II), crystallizes with two independent molecules lying across twofold rotation axes in the space group C2/c, and the molecules are conformationally chiral; there are no direction‐specific intermolecular interactions in the crystal structure of (II).